Frida Kahlo, La chair ouverte - Julie Crenn (Genre & Histoire)
The article deals with the political commitment and with the report of identification of Frida Kahlo (1907-1954) with strong feminine figures of the Mexican culture, that they are legendary or historic. This phenomenon retranscribed in her paintings allowed her to investigate themes such as the body of the women, women’s condition or still the oppressive patriarcalism. She expressed women’s suffer of loosing child, desperate women, different kind of wounds (wounds of body and wounds of sentiments) through several self-portraits. She did not hesitate to draw from her personal experience to deal with subjects considered as taboos in the years 1930-1950, what makes of her a premature feminist artist symbolizing the American slogan lauded at the beginning of 1970’s « The personal is political ».